TINJAUAN HUKUM PERJANJIAN YANG TELAH DALUWARSA TERHADAP UTANG-PIUTANG YANG DILAKUKAN DI BAWAH TANGAN BERDASARKAN HUKUM POSITF DI INDONESIA(Contoh Kasus Putusan Pengadilan Negeri Jakarta Pusat Nomor 538/Pdt.G/2014/PN.JKT.PST) - Imelda Septy Febrian; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2018)
In practice, borrowing money is one of the means to get funds needed by humans. However, with the development of the era of borrowing and borrowing, there must be strong evidence to prove that there has been a loan lending event. in practice the agreement is carried out either in writing or by word of mouth or written under the hand, in accordance with the demand for it must be made in the presence of good faith and legal certainty. In making an agreement usually given a predetermined period of time based on the agreement of the parties. And if the agreement has expired the time period has been set then in the agreement the debt is past its term. But in this case the agreement was expired and the creditor had only collected the debt to the debtor for 34 years. What if the creditor collects the debt that has passed this time and in the Islamic law the debt must be paid even though the person who has the debt has died. The author examines this problem by using normative legal research methods supported by interviews with people who are experts in the field of Islamic law and law. In this agreement, it can cause losses to the creditor. As a result, in Article 1362 of the Civil Code, it is said that if a default occurs, there is a compensation.